Human Urine-Derived Stem Cells: Potential for Cell-Based Therapy of Cartilage Defects - Long Chen; Lang Li; Fei Xing; Jing Peng; Kun Peng; Yuanzheng Wang; Zhou Xiang (Stem Cells International)
Stem cell therapy is considered an optimistic approach to replace current treatments for cartilage defects. Recently, human urine-derived stem cells (hUSCs), which are isolated from the urine, are studied as a promising candidate for many tissue engineering therapies due to their multipotency and sufficient proliferation activities. However, it has not yet been reported whether hUSCs can be employed in cartilage defects. In this study, we revealed that induced hUSCs expressed chondrogenic-related proteins, including aggrecan and collagen II, and their gene expression levels were upregulated in vitro. Moreover, we combined hUSCs with hyaluronic acid (HA) and injected hUSCs-HA into a rabbit knee joint with cartilage defect. Twelve weeks after the injection, the histologic analyses (HE, toluidine blue, and Masson trichrome staining), immunohistochemistry (aggrecan and collagen II), and histologic grade of the sample indicated that hUSCs-HA could stimulate much more neocartilage formation compared with hUSCs alone, pure HA, and saline, which only induced the modest cartilage regeneration. In this study, we demonstrated that hUSCs could be a potential cell source for stem cell therapies to treat cartilage-related defects in the future.